Fundamentals of Entrepreneurship (ENT 300) : MustLihat photocopy & printing shop / Mohd Rafiq Safiuddin Safri … [et al.] - Safri, Mohd Rafiq Safiuddin; Hamdan, Jamaly Hamsyah; Njau, John Langgang; Gumin, Cyril Legew
Our company name is MustLihat Photocopy Shop. The business of our company has been decided on the form of partnership. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to offers services by photocopy, printing banner, and printing all sorts of file. Other than that, we also sell stationaries and snacks. All partners are encourage and entitled to participate in all business management. We have agreed that MOHD RAFIQ SAFIUDDIN BIN SAFRI as the General Manager and Administrative Manager, JAMALY HAMSYAH BIN HAMDAN as the Marketing Manager, JOHN LANGGANG NJAU as the Operation Manager, and CYRIL LEGGEW GUMIN as the Financial Manager. The selection of each position is based on consensus among all partners and selected based on their skills and experience.